Rancang Bangun Website Coin Laundry Alhamdulillah - Saputra, Andi Maghfirah Inzani; Ilahi, Indah Kurnia; Kartika, Selviani Amalia; Hikmah, Nur; Butar-butar, Martahan Mikhael; Sampetoding, Eliyah A M; Ayatullah, Usamah bin; Gormantara, Jeriko; Ardhana, Valian Yoga Pudya; Mulyodiputro, M. Dermawan (SainsTech Innovation Journal, 2022)
The laundry business has now developed a lot, especially in campus and office areas. The laundry business is one of the businesses that has a great opportunity for business actors because when students or other people do not have time to wash their own clothes, they will hand them over to a washing service, namely laundry. In this journal we designed a website that can make it easier for cashiers to make transactions. In analyzing and building the system we use SDLC Waterfall Modell as our reference and have also displayed the Project Management Office (PMO). There are several other stages in designing, namely there are activity diagrams, use case diagrams, sequence diagrams, DFD, and also mock up websites that we have attached to this journal.